2020
DOI: 10.18632/aging.103081
|View full text |Cite
|
Sign up to set email alerts
|

A novel dipeptide from potato protein hydrolysate augments the effects of exercise training against high-fat diet-induced damages in senescence-accelerated mouse-prone 8 by boosting pAMPK / SIRT1/ PGC-1α/ pFOXO3 pathway

Abstract: The pathological effects of obesity are often severe in aging condition. Although exercise training is found to be advantageous, the intensity of exercise performed is limited in aging condition. Therefore in this study we assessed the effect of a combined treatment regimen with a short-peptide IF isolated from alcalase potato-protein hydrolysates and a moderate exercise training for 15 weeks in a 6 month old HFD induced obese senescenceaccelerated mouse-prone 8 (SAMP8) mice model. Animals were divided into 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“… 174 , 190 Furthermore, in an animal study, 15-week moderate AT has been shown to confront metabolic disorders by suppressing TNF-α signaling responses and also promoting muscle energy-sensing network proteins, including AMPK, Sirtuin-1, PPARγ Co-Activator 1α (PGC-1α). 191 …”
Section: Introductionmentioning
confidence: 99%
“… 174 , 190 Furthermore, in an animal study, 15-week moderate AT has been shown to confront metabolic disorders by suppressing TNF-α signaling responses and also promoting muscle energy-sensing network proteins, including AMPK, Sirtuin-1, PPARγ Co-Activator 1α (PGC-1α). 191 …”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic hydrolysis is an attractive approach for utilizing proteins to achieve increased value [ 11 , 12 ]. Specifically, proteolysis is capable of breaking proteins into peptides with desired size, charge, and surface hydrophobic properties and further improving their antioxidative properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, SIRT1/PGC-1α signaling pathway activation can promote cell survival 69 . Exercise training upregulates SIRT1/PGC-1α/AMPK (AMP-activated protein kinase) and prolongs cell longevity 70 . Second, SIRT1 can attenuate ER stress-induced heart injury and cell apoptosis by interacting with eIF2α and inducing deacetylation of the lysine site (K141 and K143), which leads to protein kinase R-like endoplasmic reticulum kinase (PERK)/ eIF2α pathway inactivation 71 .…”
Section: Pivotal Targets Identified From Exercised Heartmentioning
confidence: 99%